Flutuação populacional e iscas para monitoramento de Cosmopolites sordidus (Germar) e Metamasius hemipterus (Linnaeus) (Coleoptera: Curculionidae) em bananal - Santos, Ivone Beatryz dos (2014)
Weevils attack is one of the major factors responsible for low yield of brazilian banana plantations. Among them, there is the banana weevil Cosmopolites sordidus (Germar, 1824) (Coleoptera:Curculionidae), considered a major pest of banana, meet up widespread, causing damage in all producing countries, and Metamasius hemipterus (Linnaeus,1758) (Coleoptera: Curculionidae), which in recent years has emerged as pest in banana plantation. Periodic monitoring of the population of these insects contribute to reduce the damage caused in banana plants, therefore, it becomes the producer to intervene in the management of the crop before the insect reaches the economic injury level. This present study aimed to evaluate the efficiency of attractive baits for catching insects of the family Curculionidae, as well as monitor the population dynamics of C. sordidus and M. hemipterus on commercial banana plantation cv. Nanicão, in dry and rainy season, from May 2012 to April 2013, in conditions of the Amazon biome. Three treatments were used: 1) synthetic aggregation pheromone - as control; 2) sugarcane molasses and 3) sugarcane pieces, disposed in plots of 0.5 hectare each one. Among the tested baits, sugarcane molasses and sugarcane pieces were not effective to capture C. sordidus. However, the attractive bait sugarcane pieces proved efficient for monitoring and massal collect M. hemipterus in banana plantation. The population dynamics of C. sordidus, was positively influenced by rainfall, with higher population levels in the rainy season. Compared to M. hemipterus was observed that the insect population did not suffer any influence of climatic variables.